นวัตกรรมและเทคโนโลยีสารสนเทศสำหรับครูในศตวรรษที่ 21 - ทิพโชติ, พรรณนิดา; ศิลากุล, ดวงพร; เทศน์ธรรม, วิภาษณ์ (วารสาร มมร ยศสุนทรปริทรรศน์, 2024)
This article reflects the context of information technology playing a crucial role in education and learning. However, using technology effectively and responsibly requires good morals and ethics, especially in the role of teachers who are educational leaders and role models for students. Using teaching materials with integrity is essential in developing students to possess both knowledge and moral values. Here are methods teachers can employ to use teaching materials ethically to develop their students. Utilizing teaching materials with integrity is something teachers should prioritize to develop students into individuals who possess both knowledge and moral values. Selecting appropriate materials, respecting copyrights, creating innovative content, and promoting ethical values through teaching are methods teachers can adopt to cultivate well-rounded students.